EVALUATION OF THE JKN MOBILE APPLICATION USING THE EUCS METHOD AT RSU ANNA MEDIKA MADURA BANGKALAN DISTRICT - Eka Suci Daniyanti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
JKN Mobile Application is a means of information for JKN or BPJS Health participants. Evaluation of the use of the JKN Mobile application that supports JKN programme services needs to be done so that the application can continue to be used and as a recommendation for future application improvements. The type of research is quantitative with an analytical survey approach using a cross sectional design. Population in this study were all BPJS health participants in Bangkalan Regency who used the Mobile JKN application. The sampling technique in this study was accidental sampling. Evaluation using the EUCS method is used to provide an assessment of user satisfaction with system quality. Results of hypothesis testing on the variables of concent, accuracy, format, ease of use, timeliness and user satisfaction show that each of these variables has a sign value. <0.05, which means that the hypothesis of each variable is accepted (Ha). JKN mobile application already displays clear information, is easy to understand, provides accurate information, a good and attractive appearance and ease of understanding, ease of use and accuracy of displaying the latest information so as to provide user satisfaction with the application. Improving the performance of the JKN mobile application is necessary to maintain service quality and aims to increase the satisfaction of users of the application.